HIGH INTERACTION OF ELEMENTARY SCHOOL STUDENTS WITH GADGETS: HOW DOES THEIR SOCIAL GROWTH? - Faradibah, Faradibah; Krismanto, Wawan; Musfirah, Musfirah; Halik, Abdul; Pasinggi, Yonathan S.; Tuken, Ritha (JURNAL EDUSCIENCE, 2025)
Purpose – The students who frequently use gadgets tend to be more individualistic and less concerned about the needs of friends or others. This interferes with the formation of social attitudes that are essential for a student's character development. Therefore, this study will describe the phenomenon, focusing on answering research questions: How is the intensity of gadget use among 6th-grade students? Moreover, what is the impact of gadget use on the social attitudes of 6th-grade students?Methodology – Qualitative descriptive methods were used in this study. The participants were 6th-grade students. They were then observed and interviewed in depth, including their parents, teachers, and principal. Data were collected using surveys, interviews, observation, and documentation techniques. The research data were analyzed in three stages: data condensation, data display, and conclusions.Findings – The results showed that the level of gadget use among 6th-grade students at Mentari Public Elementary School, Kota Parepare, South Sulawesi, was relatively high. The high interaction of two students with these gadgets has a significant negative impact on students' social attitudes. The impacts are making them less physically and more focused on gadgets. They experience decreased communication skills, especially in face-to-face situations. They tend to be less confident, less fluent in speaking, and often not focused when invited to communicate. It also distracts students from their responsibilities and makes students more aggressive and less polite when interacting with others.Contribution – Based on research data and a review of various literature, it is evident that high-intensity gadget use poses potential problems for the social growth of elementary school children. This study shows a variety of these problems. This contributes to scientific studies on children's social growth and the use of gadgets among children.